TRBP and eIF6 Homologue in Marsupenaeus japonicus Play Crucial Roles in Antiviral Response - Wang, Shuai; Chen, An-Jing; Shi, Li-Jie; Zhao, Xiao-Fan; Wang, Jin-Xing (PLOS ONE, 2012)
Plants and invertebrates can suppress viral infection through RNA silencing, mediated by RNA-induced silencing complex (RISC). Trans-activation response RNA-binding protein (TRBP), consisting of three double-stranded RNA-binding domains, is a component of the RISC. In our previous paper, a TRBP homologue in Fenneropenaeus chinensis (Fc-TRBP) was reported to directly bind to eukaryotic initiation factor 6 (Fc-eIF6). In this study, we further characterized the function of TRBP and the involvement of TRBP and eIF6 in antiviral RNA interference (RNAi) pathway of shrimp. The double-stranded RNA binding domains (dsRBDs) B and C of the TRBP from Marsupenaeus japonicus (Mj-TRBP) were found to mediate the interaction of TRBP and eIF6. Gel-shift assays revealed that the N-terminal of Mj-TRBP dsRBD strongly binds to double-stranded RNA (dsRNA) and that the homodimer of the TRBP mediated by the C-terminal dsRBD increases the affinity to dsRNA. RNAi against either Mj-TRBP or Mj-eIF6 impairs the dsRNA-induced sequence-specific RNAi pathway and facilitates the proliferation of white spot syndrome virus (WSSV). These results further proved the important roles of TRBP and eIF6 in the antiviral response of shrimp.